Nucleotide and amino acid sequences of a coat protein of an Ukrainian isolate of Potato virus Y: comparison with homologous sequences of other isolates and phylogenetic analysis - Budzanivska, I.G.; Ovcharenko, L.P.; Kharina, A.V.; Boubriak, I.I.; Polischuk, V.P. (Вiopolymers and Cell, 2014)
Aim. Identification of the widespread Ukrainian isolate(s) of PVY (Potato virus Y) in different potato cultivars and subsequent phylogenetic analysis of detected PVY isolates based on NA and AA sequences of coat protein. Methods. ELISA, RT-PCR, DNA sequencing and phylogenetic analysis. Results. PVY has been identified serologically in potato cultivars of Ukrainian selection. In this work we have optimized a method for total RNA extraction from potato samples and offered a sensitive and specific PCR-based test system of own design for diagnostics of the Ukrainian PVY isolates. Part of the CP gene of the Ukrainian PVY isolate has been sequenced and analyzed phylogenetically. It is demonstrated that the Ukrainian isolate of Potato virus Y (CP gene) has a higher percentage of homology with the recombinant isolates (strains) of this pathogen (approx. 98.8– 99.8 % of homology for both nucleotide and translated amino acid sequences of the CP gene). The Ukrainian isolate of PVY is positioned in the separate cluster together with the isolates found in Syria, Japan and Iran; these isolates possibly have common origin. The Ukrainian PVY isolate is confirmed to be recombinant. Conclusions. This work underlines the need and provides the means for accurate monitoring of Potato virus Y in the agroecosystems of Ukraine. Most importantly, the phylogenetic analysis demonstrated the recombinant nature of this PVY isolate which has been attributed to the strain group O, subclade N:O. Мета. Виявлення українських ізолятів Y вірусу картоплі (PVY) у різних сортах картоплі і їхній наступний філогенетичного аналіз на основі нуклеотидних і амінокислотних послідовностей білка оболонки. Методи. ІФА, ЗТ-ПЛР, секвенування ДНК і філогенетичний аналіз. Результати. У зразках картоплі вітчизняної селекції методом ІФА ідентифіковано PVY. Оптимізовано процес виділення РНК та розроблено тест-систему на базі ПЛР для діагностики українських ізолятів PVY. Секвеновано ділянку гена капсидного білка українського ізоляту та здійснено філогенетичний аналіз. Встановлено, що зазначений ген демонструє вищий ступінь гомології з генами капсидних білків рекомбінантних ізолятів (штамів) (98,8–99,8 % гомології для нуклеотидних і амінокислотних послідовностей). Український ізолят перебуває в окремому кластері разом з рекомбінантними ізолятами із Сирії, Ірану та Японії і має з ними спільне походження. Висновки. В результаті роботи визначено засоби для точного моніторингу вірусу картоплі в агроекосистемах України. Філогенетичний аналіз продемонстрував рекомбінантну природу досліджуваного ізоляту PVY, який раніше був приписаний до групи штамів О, субклади N:О. Цель. Выявление украинских изолятов Y вируса картофеля (PVY) в различных сортах картофеля и их последующий филогенетический анализ на основе нуклеотидных и аминокислотных последовательностей белка оболочки. Методы. ИФА, ОТ-ПЦР, секвенирование ДНК и филогенетический анализ. Результаты. В образцах картофеля отечественной селекции методом ИФА идентифицирован PVY. Оптимизирован процесс выделения РНК и разработана тест-система на базе ПЦР для диагностики украинских изолятов PVY. Секвенирован участок гена капсидного белка украинского изолята и проведен филогенетический анализ. Показано, что указанный ген демонстрирует высокую степень гомологии с генами капсидных белков рекомбинантных изолятов (штаммов) (98,8–99,8 % гомологии для нуклеотидных и аминокислотных последовательностей). Украинский изолят находится в отдельном кластере вместе с рекомбинантными изолятами из Сирии, Ирана и Японии и имеет с ними общее происхождение. Выводы. В результате работы определены средства для точного мониторинга вирусов картофеля в агроэкосистемах Украины. Филогенетический анализ продемонстрировал рекомбинантную природу исследуемого изолята PVY, который ранее был приписан к группе штаммов О, субклады N:O.